Vibrio Dynamics and Health Status of Pacific White Shrimp Fed with Cinnamaldehyde-Containing Feed - Dian Eka Ramadhani; Andri Hendriana; Dinamella Wahjuningrum; Muhammad Arif Mulya (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research